Gorham–Stout disease of the temporal bone involving the temporomandibular joint. Issue 3 (24th January 2018) - Mulvihill, D; Kumar, R S; Muzaffar, J; Irving, R
Abstract: Background: Gorham–Stout disease of the skull is a very rare entity. It presents with gradual bone resorption, and proliferation of lymphoid and vascular channels within the bony matrix. This is often a diagnosis of exclusion confirmed with serial imaging and based on radiological evidence. Case report: A case of Gorham–Stout disease of the temporal bone involving the temporomandibular joint, and presenting with sensorineural hearing loss and recurrent temporomandibular joint dislocation, is reported. The findings are presented and the literature on this condition is reviewed. Conclusion: ENT and maxillofacial surgeons should be aware of this extremely rare cause of temporomandibular joint dislocation and ear symptoms. Imaging comprising computed tomography and magnetic resonance imaging is crucial to achieving a diagnosis, which may only become evident after repeated imaging follow up. Symptomatic treatment is advised, with the option of anti-osteoclastic medication and radiotherapy indicated for advanced cases. Surgery is only recommended for complications including involvement of neurovascular structures.